Neural Stem Cell-Derived Exosomes Improve Neurological Function in Rats with Cerebral Ischemia-Reperfusion Injury by Regulating Microglia-Mediated Inflammatory Response - Zhao X; Zhu J; Chen S; Liu R; Long T (Dove Medical Press, 2023)
Xue Zhao,* Junde Zhu, Shan Chen,* Ruojing Liu, Tingting Long Department of Human Anatomy, School of Basic Medicine, Guizhou Medical University, Guiyang, People's Republic of China*These authors contributed equally to this workCorrespondence: Junde Zhu, Department of Human Anatomy, School of Basic Medicine, Guizhou Medical University, Guian New Area, Guiyang, 550025, People's Republic of China, Tel +86-851-88416251, Email jdzhu73@126.comPurpose: To investigate the effect of neural stem cell-derived exosomes (NSC-Exos) on neural function after rat cerebral ischemia-reperfusion injury by regulating microglia-mediated inflammatory response.Methods: SD rats were randomly divided into Sham group, IRI group, PBS group and NSC-Exos group. Each group was divided into 1d, 3d, 7d and 14d subgroups. In the Sham group, only cervical vessels were isolated without blockage. MCAO model was constructed in the other three groups by blocking middle cerebral artery with thread embolism. PBS group and NSC-Exos group were, respectively, injected into the lateral ventricle of PBS and Exos. Neurobehavioral deficit scores were performed for each subgroup at relative time points, then brains were taken for TTC staining, parietal cortex histopathology and microglia-mediated inflammatory response-related factors were detected.Results: Compared with Sham group, neurological defect score and infarction volume in both the IRI and PBS groups were significantly increased. The exploration target quadrant time and escape latency time of maze test were increased. The number of CD86+/Iba1+ double-positive cells increased, while CD206+/Iba1+ double-positive cells decreased. The expressions of IL-6 and CD86 in parietal cortex were increased, while the expressions of Arg1 and CD206 were decreased. Compared with the IRI group and PBS group, neurological defect score and infarction volume in NSC-Exos group were decreased. The exploration target quadrant time and escape latency time of water maze test were decreased. The number of CD206+/Iba1+ double-positive cells increased, while CD86+/Iba1+ double-positive cells decreased. The expressions of Arg1 and CD206 in parietal cortex were increased, while the expressions of IL-6 and CD86 were decreased.Conclusion: NSC-Exos can promote the polarization of microglia, that is, inhibit the polarization of M1 and promote polarization of M2, reduce microglia-mediated neuroinflammation, suggesting that NSC-Exos may be a strategy for the treatment of microglia-mediated neuroinflammation after ischemic brain injury.Graphical Abstract: Keywords: cerebral ischemia, neural stem cell, exosome, microglia, neuroinflammation